2018
DOI: 10.1515/joc-2017-0120
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Different Optical Amplifiers in Spectrum Sliced Free Space Optical Link

Abstract: Free space optics (FSO) is well-competent and premier technology to cater the high speed services in different geographical areas such as hilly areas and inter building network. In this paper, we successfully demonstrated the spectrum sliced wavelength division multiplexed FSO system. In order to make system bandwidth efficient, frequency spacing of 75 GHz is taken among the wavelength division multiplexing (WDM) channels. Carrier spectrum broadening is achieved for spectrum slicing through the nonlinearity ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The line coding techniques implemented are return to zero (RZ), and non-return to zero (NRZ). For ampli cation of the signal in SS-WDM-FSO system, the performance of various ampli ers such as raman ampli ers, semiconductor optical ampli ers, and erbium-doped ber ampli ers were investigated and reported that eye-opening of the SS-WDM system using the later is the best compared to the rest of the ampli ers (Aditi Thakur et al 2017). SS-WDM with 10 Gbits/s Modi ed duo binary return to zero (MDRZ) for the downlink and OOK (On-Off keying) non-return to Zero (NRZ) for the uplink was proposed (S. Magidi et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The line coding techniques implemented are return to zero (RZ), and non-return to zero (NRZ). For ampli cation of the signal in SS-WDM-FSO system, the performance of various ampli ers such as raman ampli ers, semiconductor optical ampli ers, and erbium-doped ber ampli ers were investigated and reported that eye-opening of the SS-WDM system using the later is the best compared to the rest of the ampli ers (Aditi Thakur et al 2017). SS-WDM with 10 Gbits/s Modi ed duo binary return to zero (MDRZ) for the downlink and OOK (On-Off keying) non-return to Zero (NRZ) for the uplink was proposed (S. Magidi et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The linecoding techniques implemented are return to zero (RZ), and non-return to zero (NRZ). For ampli cation of the signal in SS-WDM-FSO system, the performance of various ampli ers such as Raman ampli ers, semiconductor optical ampli ers, and erbium-doped ber ampli ers were investigated and reported that eye-opening of the SS-WDM system using the later is the best compared to the rest of the ampli ers [9]. SS-WDM with 10Gbits/s power e cient advanced modulation format, modi ed duo binary return to zero (MDRZ) for the downlink and OOK (on-off keying) non-return to zero (NRZ) for the uplink was proposed [10].…”
Section: Introductionmentioning
confidence: 99%
“…In WDM technology, distinct laser is used for each channel which makes the transmission system costly and complex whereas spectrum-slicing based WDM system is a less complex and cost-effective technique which utilizes multiple intensity channels at distinct frequencies. 13 Spectrum-slicing can be realized by amplified spontaneous emission (ASE) noise in semiconductor optical amplifier 14,15 and arrayed waveguide grating. 16 The work in Ref.…”
Section: Introductionmentioning
confidence: 99%